Ping times: Relating economic growth to internet connectivity - Smit, Martijn (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2022)
Since the last decade of the twentieth century, internet access has become a sine qua non for businesses. IT as well as online commerce have been growing fast over the past decades, and many other sectors also depend more and more on internet access; even industrial services such as design and warehousing, to name but two examples, rely on and benefit from cooperation at a distance. The global boost in teleworking and particularly teleconferencing following the Covid-19 pandemic has shown how important reliable connections are.Governments have over the past decade invested in improving their connections to the worldwide internet. Yet it is not clear whether economic clustering in fact is attracted to well-connected locations. We therefore test empirically whether the level of connectedness to the global IT infrastructure has a correlation with subsequent economic growth in sectors that use such infrastructure, or even depend on it.We do this using a panel of US cities, in which we zoom in on a few sectors that can use the infrastructure and compare them against the background of other sectors in the same cities. As a measure for the quality of local connections, we employ a unique method: we use the latency (ping times), a network metric usually spurned in favour of the more common bandwidth.